Portrait of Integrity Character in Prospective Clergy Students - Hidajat, Irwan; Suryadi, Ace; Dahliyana, Asep (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2025)
Integrity is an essential character that every prospective clergy must have. In the context of higher education, especially theological higher education institutions, the formation of integrity becomes an integral part of the process of forming students' personalities. This study aims to describe the character portrait of integrity in prospective clergy students at the Sekolah Tinggi Teologi Amanat Agung, Jakarta. This study uses a descriptive quantitative approach with a survey method. The research respondents were 58 students of the Sarjana Teologi study program. The research instrument was a questionnaire developed based on the dimensions of integrity according to the concept of personal integrity, namely honesty, moral consistency, responsibility, and moral courage. The data were analyzed using descriptive statistical techniques to map the tendencies of the respondents' integrity characters. The results of the study showed that most prospective clergy students had a high level of integrity in the aspects of honesty and responsibility, but there were still weaknesses in the aspect of moral courage in facing situations that demanded difficult ethical decision-making. These findings indicate that the process of forming integrity in prospective clergy requires further strengthening, especially through a seminary-based learning approach. This study is expected to be a reference for theological higher education institutions in compiling a character formation curriculum that is more effective and relevant to the needs of the times.